2005
DOI: 10.1093/cercor/bhi084
|View full text |Cite
|
Sign up to set email alerts
|

Different Functional Loops between Cerebral Cortex and the Subthalmic Area in Parkinson's Disease

Abstract: We investigate the extent to which functional circuits coupling cortical and subthalamic activity are multiple and segregated by frequency in untreated Parkinson's disease (PD). To this end, we recorded EEG and local field potentials (LFPs) from macroelectrodes inserted into the subthalamic nucleus area (SA) in nine awake patients following functional neurosurgery for PD. Patients were studied after overnight withdrawal of medication. Coherence between EEG and SA LFPs was apparent in the theta (3-7 Hz), alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
154
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(188 citation statements)
references
References 71 publications
28
154
1
2
Order By: Relevance
“…The magnitude of ␤ coherence, however, was below 16% and thereby much lower than in the theta band. Values of similar magnitude were reported for ␤ coherence between scalp EEG and recording sites in the cerebellar thalamus (Marsden et al, 2000;Paradiso et al, 2004) and basal ganglia (Marsden et al, 2001;Williams et al, 2002;Fogelson et al, 2006), indicating that activity at these sites also interacts with cortical activity. Anatomically and functionally, the main output of the basal ganglia occurs via the pallidothalamic and nigrothalamic tract to the thalamus.…”
Section: Thalamocortical Interplaysupporting
confidence: 70%
See 1 more Smart Citation
“…The magnitude of ␤ coherence, however, was below 16% and thereby much lower than in the theta band. Values of similar magnitude were reported for ␤ coherence between scalp EEG and recording sites in the cerebellar thalamus (Marsden et al, 2000;Paradiso et al, 2004) and basal ganglia (Marsden et al, 2001;Williams et al, 2002;Fogelson et al, 2006), indicating that activity at these sites also interacts with cortical activity. Anatomically and functionally, the main output of the basal ganglia occurs via the pallidothalamic and nigrothalamic tract to the thalamus.…”
Section: Thalamocortical Interplaysupporting
confidence: 70%
“…LFP recordings come mainly from sites in the cerebellar thalamus (Marsden et al, 2000;Paradiso et al, 2004) or in the basal ganglia (Marsden et al, 2001;Williams et al, 2002;Fogelson et al, 2006) and reflect the sites of surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Because higher WC was found in temporo-parietal channel pairs in the PD-D group, this abnormal synchrony might result from impairment of the sensorimotor cortex. Abnormal synchrony might cause motor symptoms such as tremors [36,49]. Several studies have reported that high WC might result from synchrony of thalamo-cortical oscillatory activity due to the deterioration of the substantia nigra in PD patients [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular note, reduction in the power of cortical beta-band activity during motor preparation scales with the directional uncertainty of forthcoming movement, and this in turn correlates with the change of latency with response uncertainty (Tzagarakis et al, 2010). Other limitations are the presumptive localization of electrode contacts in the STN (Williams et al, 2002;Fogelson et al, 2006) and the possibility that power changes picked up at the bipolar contacts of the DBS electrode are not really focally generated. Against the latter, we found a steep gradient in LFP power in the beta band across different bipolar contact pairs consistent with a local generator (Kühn et al, 2004(Kühn et al, , 2006, although the strongest argument in favor of the local generation of beta activity in the LFP is the demonstration that the discharge of neurons in the STN tends to be locked to it (Levy et al, 2002;Kühn et al, 2005).…”
Section: Discussionmentioning
confidence: 99%